PULMONARY MANIFESTATION OF SARCOIDOSIS DETECTED ON HIGH RESOLUTION COMPUTED TOMOGRAPHY - Dimitrijevikj, Kristina; Mitrevska, Nadica; Nikolova, Sonja; Janevski, Petar; Pashoska, Milkica (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Sarcoidosis is a multisystemic disease of unknown etiology that mostly affects the lung parenchyma with interstitial and granulomatous changes of varying intensity and expression depending on the stage of the disease. In addition to the parenchyma and interstitium, the mediastinal lymph nodes are also very often affected. To analyze the distribution and characteristics of interstitial lung lesions and the involvement of mediastinal lymph nodes in pulmonary sarcoidosis by the method of high-resolution computed tomography. 15 patients diagnosed with pulmonary sarcoidosis were included in the study. Computed tomography with high resolution was made on 128 slice CT scanner PHILIPS INCISIVE, using 1 mm thin-slice thickness and high spatial frequencies algorithm for image reconstruction. Lymph nodes are classified as hilar and mediastinal with a maximum diameter of short axis of more than 10 mm taken as their enlargement. Pulmonary changes are classified as nodules, reticular opacities, fibrous lesions, ground glass opacities and consolidations. The predominant distribution of lesions in the upper and middle zones of the lungs compared to the lower zones was noted. The disease is graded in 5 stages with the Scadding classification. 15 cases of patients diagnosed with sarcoidosis were analyzed all of whom are women in the age group of 30-60 years old. Two patient are in stage I and three are in III stage of the disease, 6 patients are in stage II of sarcoidosis and 4 are in stage IV of the disease. Dry cough as a symptom predominates in all patients, while dyspnea is graded according to the mMRC scale. Mediastinal lymphadenopathy with and without calcifications was present in 11 patients. The type of lung changes as well as their distribution are presented in graphs.HRCT is the method of choice in the evaluation of pathological changes in pulmonary sarcoidosis. It very precisely shows us the characteristic appearance of nodules and lesions, their distribution and atypical changes and helps us in grading the disease and its treatment. Key words: lung, sarcoidosis, interstitial lung disease, HRCT.